COVID-19 Associated Multisystem Inflammatory Syndrome in Children (MIS-C): A New Pediatric Alert - Sharmin Shova, Shamima; Islam, Mohammad Imnul (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Multisystem inflammatory syndrome in children (MIS-C), also termed pediatric multisystem inflammatory syndrome (PMIS) temporally associated with coronavirus disease-2019 (COVID-19) is rare but an emerging alarming condition. Though the exact pathogenesis is unknown, COVID-19 can trigger the condition directly or indirectly via immune complex mediated or antibody-dependent enhancement. Patients with MIS-C can present with persistent fever and a constellation of symptoms including hypotension, multiorgan involvement and elevated inflammatory markers. Presentations of MIS-C have overlapping features of Kawasaki disease (KD), toxic shock syndrome (TSS) and Kawasaki disease shock syndrome. Age of presentation, features of shock and more predilections for myocardial dysfunction can distinguish MIS-C from Kawasaki disease. Early recognition is essential, followed by prompt admission to the hospital for specialist attention. Admission to a pediatric intensive unit is mandatory for children with hemodynamic instability (shock, arrhythmia), significant respiratory compromise, or other potentially life-threatening complications. It is also necessary to maintain an appropriate follow-up schedule to observe the long-term outcome. The prognosis of PMIS/ MIS-C is uncertain, given that it is a new clinical entity and understanding of the disease is still evolving. J Bangladesh Coll Phys Surg 2021; 39: 249-260